Implementasi Metode Iqro' Dalam Meningkatkan Kemampuan Membaca Al-Qur’an - Firdaus, Mohammad; Fitri, Ainul (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2024)
The problem raised in this research is how to implement the Iqro’ Method carried out at Junior High School TMI Al-Amien Prenduan improving the ability to read the holy qur’an in an effort to overcome female students who are not fluent in reading the Al-Qur’an according to the correct rules. Which is described in two focuses,namely : 1. How to implement the iqro’ method in improving the holy qur’an reading skills of tmi Al-Amien Prenduan in 2022-2023.2. How does implemening the iqro’ method contribute to improving the holy qur’an reading ability of Al-Amien Prenduan students in 2022-2023.